2023
DOI: 10.55446/ije.2023.778
|View full text |Cite
|
Sign up to set email alerts
|

ELUCIDATING THE HOST PREFERENCE BY THE PULSE BEETLE <i>CALLOSOBRUCHUS CHINENSIS</i> (L)

Abstract: Callosobruchus chinensis (Bruchidae: Coleoptera) known as pulse beetle is a serious pest of pulses causing economic losses. The present work reports the effect of pulses on life cycle parameters (oviposition, emergence, longevity, total development period) of Callosobruchus chinensis (L.), and also on the nutritional loss incurred by it. Grains of seven pulses viz. Vigna radiata (green gram), Vigna aconitifolia (moth bean), Cicer arietinum (desi chickpea), Vigna unguiculata (cowpea), Cajanus cajan (pigeon pea)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Highest reduction in carbohydrates contents (44.59 to 31.38%) was found in Thal-2006 variety, whereas relatively lowest reduction was noted in Punjab-2009 variety. Current findings are in agreement with Sharma et al (2023) who found reduction in carbohydrates in chickpea grains after C chinensis infestation. Results of this study are similar to those of Deepika et al (2020) who found carbohydrates loss from 37.67 to 48.65%.…”
Section: Carbohydratessupporting
confidence: 93%
“…Highest reduction in carbohydrates contents (44.59 to 31.38%) was found in Thal-2006 variety, whereas relatively lowest reduction was noted in Punjab-2009 variety. Current findings are in agreement with Sharma et al (2023) who found reduction in carbohydrates in chickpea grains after C chinensis infestation. Results of this study are similar to those of Deepika et al (2020) who found carbohydrates loss from 37.67 to 48.65%.…”
Section: Carbohydratessupporting
confidence: 93%